Riverbend Romance: Riverbend Gap - Book 1 - Hunter, Denise, 1968- (Thorndike, Maine : Center Point Large Print, 2021)
"When Katie Lovelands car veered off a winding Appalachian Mountain road, she thought she was done for. That is until Cooper Robinson, local sheriffs deputy, came to her rescue. And though Katie narrowly escaped her brush with death, she still fell. Hard. She wasnt the only one. But soon Cooper learns that the woman hes more attracted to than any hes ever met is his brothers new girlfriend -- and therefore unquestionably off limits. Yet, despite his best efforts, Cooper and Katie cant seem to avoid running into each other. Or ignore the undeniable chemistry between them. As they grow closer, Katie shares the secrets of her past and the real reason she moved to their small North Carolina town. She also wins over Coopers welcoming and bighearted family. But they dont know that her feelings for Cooper keep growing -- all while shes dating his brother. Soon the stakes of their emotional connection become higher than either of them could have imagined. Katie stands to lose the first family shes ever had, and a scandal could doom Coopers campaign for sheriffs office. Suddenly they find themselves on the edge of another precipice -- and theyre forced to make a decision that could change their lives forever"-- Provided by publisher.
Keywords: Rescues -- Fiction; Sheriffs -- Fiction; Brothers -- Fiction; Birthmothers -- Fiction; Traffic accidents -- Fiction; Life change events -- Fiction; Man-woman relationships -- Fiction; Appalachian Trail -- Fiction; North Carolina -- Fiction; Christian fiction; Christian fiction; Romance fiction; Love stories